CD81 is a receptor for equine arteritis virus (family: Arteriviridae) - Sara M. Maloney; Teressa M. Shaw; Kylie M. Nennig; Malorie S. Larsen; Aadit Shah; Ashish Kumar; Joseph Marcotrigiano; Joe Grove; Eric J. Snijder; Robert N. Kirchdoerfer; Adam L. Bailey (mBio)
ABSTRACT Arteriviruses are a family of single-stranded, positive-sense RNA (+ssRNA) viruses that infect diverse animal hosts. Many arteriviruses are macrophage-tropic, consistent with their utilization of the macrophage-specific molecule CD163 as a receptor. However, the horse arterivirus (equine arteritis virus, EAV), which infects additional cell types beyond macrophages, does not utilize CD163 in its entry mechanism. Here, we use a genome-wide CRISPR knockout screen to identify alternative receptors that could explain this discrepancy in arterivirus receptor utilization and tropism, identifying the plasma membrane tetraspanin CD81 as a required host factor for EAV infection. Genetic knockout of CD81 or pre-incubation with soluble CD81 protected cells from infection with EAV, but had no impact on susceptibility to other arteriviruses. Bypassing the entry step of the viral life cycle by transfecting the EAV genome into CD81-knockout cells produced infectious EAV, implicating CD81 in the EAV entry process. Screening of CD81 orthologs from natural arterivirus hosts identified the brushtail possum CD81 as unsupportive of EAV entry, indicating that CD81 incompatibility can serve as a barrier to cross-species infection. Horse/possum CD81 chimeras were then used to map the structural domains of CD81 engaged by EAV, identifying alpha helix “D” on the large extracellular loop of CD81 as critical for EAV entry. This study identifies the first example of receptor switching in the Arteriviridae family and, given the broad tissue distribution of CD81 expression, suggests that the adoption of CD81 enabled an expansion of EAV tropism.IMPORTANCEArteriviruses are a family of diverse positive-sense RNA viruses that can infect a wide range of animal hosts, but many details regarding how arteriviruses gain entry into cells remain unclear. Most arteriviruses are thought to utilize the macrophage-specific molecule CD163 as a receptor; however, the horse arterivirus (equine arteritis virus, EAV) infects additional cell types beyond macrophages and does not utilize CD163. In this study, we identified the host factor CD81 as a significant player in EAV entry. Beyond the implications that this discovery holds for equine health, this study adds to the increasingly complex picture of arterivirus entry and demonstrates that these viruses are capable of adopting new host molecules as receptors, with consequences for the types of cells these viruses infect, the disease they cause, and their mode(s) of transmission.